Pengaruh Komitmen Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan PT. Mopoli Raya di Kecamatan Seruway - Zulkarnen Mora; Icha Fandayani; Agung Suharyanto (Mahesa Research Center, 2020)
This study aims to determine the effect of work commitment and job satisfaction on employee performance at PT. Mopoli Raya. This study uses a sample of 83 respondents who are permanent employees of PT. Mopoli Raya. Methods of data analysis using multiple linear regression equations, t test, F test and the coefficient of determination (R2). The results showed that work commitment has a positive effect on performance and if work commitment increases by one unit it will increase performance. Job satisfaction has a positive effect on performance and if job satisfaction increases by one unit it will increase performance. Work commitment has no significant effect on employee performance, job satisfaction has a significant effect on employee performance at PT. Mopoli Raya, it can be stated that the variables work commitment and job satisfaction simultaneously affect employee performance. Thus, work commitment and job satisfaction affect the performance of employees of PT. Mopoli Raya.